KINETIC STUDIES OF SUBSTITUTION ON CIS-DIAQUA-CHLOROTRIS-( DEIMETHYL SULFOXIDE)-RUTHENIUM(II) COMPLEX WITH GLYCYLGLYCINE IN AQUEOUS MEDIUM: Life Sciences-Chemistry - GHOSH, ALAK K.; MANDAL, ARUP; BERA, BIPLAB K.; MALLICK, SUBHASIS; MONDAL, SUBALA; KARMAKAR, PARNAJYOTI (International Journal of Life Science and Pharma Research, 2011)
The kinetics of interaction between glycylglycine and cis-[RuCl(Me2SO)3(H2O)2]+ have been studied spectrophotometrically as a function of [RuCl(Me2SO)3(H2O)2 +], [diglycine] and temperature at a particular pH(5.0), where the substrate complex exists predominantly as a diaqua species(in aqueous solution) and diglycine as the zwitter ion. The reaction has been found to proceed via two distinct consecutive steps i.e., it shows a non-linear dependence on the concentration of diglycine: first process is [ligand] dependent but the second step is [ligand] independent. The rate constants for the processes are: k1 10-3s-1 and k2 10-5s-1. The activation parameters were calculated from Eyring plots suggests an associative mechanism for the interaction process. From the temperature dependence of the outer sphere association equilibrium constants, the thermodynamic parameters were also calculated, which gives a negative G0 value at all temperatures studied, supporting the spontaneous formation of an outer sphere association complex.